Continuous Assessment of Labour Pain using Handgrip Force - Nadine Wickboldt (Pain Research and Management, 2015)
BACKGROUND: Assessment of dynamic changes in painful experiences, such as labour, using conventional rating scales (eg, numerical rating scale [NRS]) has limitations. An alternative for continuous pain evaluation could be a signal generated by voluntary action of the parturient. Remifentanil administration for obstetric analgesia could be improved by these dynamic measures of labour pain. In the present study, handgrip force was measured by a dynamometer to signal labour pain.